PELATIHAN DIGITAL MARKETING PADA MASYARAKAT KELURAHAN TEGALREJO KECAMATAN MEDAN PERJUANGAN - Harkim Harkim; Bambang Sugihato; Rejekia V Simanungkalit; Ilhamsyah Siregar; Maya Andriani; Agus Marwan (Jurnal Abdimas Bina Bangsa, 2023)
The aim of this community service is to increase the knowledge of the Tegalrejo sub-district community regarding the use of the internet to support marketing, or digital marketing. The implementation method for this service is through lectures on concepts related to digital marketing platforms, as well as short practice on how to pragmatically use digital marketing platforms in various fields. The expected result of this training is that the Tegalrejo sub-district community is able to skillfully apply digital marketing concepts according to their needs. In this context, it is a need in accordance with what is the concentration and interest, as well as the profession of the people of Tegalrejo. Some are for MSMEs, some are for organizations and so on